Antifungal activity of extracts and isolated compounds from Buchenavia tomentosa on Candida albicans and non-albicans - Teodoro, Guilherme R. [UNESP]; Brighenti, Fernanda Lourenção [UNESP]; Delbem, Alberto C. Botazzo [UNESP]; Delbem, Ádina Cléia B. [UNESP]; Khouri, Sonia; Gontijo, Aline Vidal L. [UNESP]; Pascoal, Aislan C. R.F.; Salvador, Marcos J.; Koga-Ito, Cristiane Y. [UNESP] (My University, 2015)
Aim: This study aimed to evaluate the antifungal activity of Buchenavia tomentosa extract and bioactive compounds on six Candida species. Materials & methods: The antimicrobial activity of extract was evaluated using standard strains and clinical isolates. Cytotoxicity was tested in order to evaluate cell damage caused by the extract. Extract was chemically characterized and the antifungal activity of its compounds was evaluated. Results: Extract showed antifungal activity on Candida species. Candida non-albicans were more susceptible than Candida albicans. Low cytotoxicity for extract was observed. The isolated compounds presented antifungal activity at least against one Candida spp. and all compounds presented antifungal effect on Candida glabrata. Conclusion: Extracts from Buchenavia tomentosa showed promising antifungal activity on Candida species with low cytotoxicity. Gallic acid, corilagin and ellagic acid showed promising inhibitory activity on Candida glabrata.
Keywords: Candida albicans; Candida non-albicans; Antifungal agents; Natural compounds